Elimination of the interfering effect of hydrogen on the determination of palladium by stripping voltammetry; Journal of Analytical Chemistry; Vol. 72, iss. 12 - Kolpakova N. A. Nina Alexandrovna; Panova S. M. Svetlana Mikhaylovna; Oskina Yu. A. Yuliya Aleksandrovna; Сабитова Ж. К. Жамиля Корганбековна (2017, 2017)
Title screen